2017
DOI: 10.18553/jmcp.2017.23.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Dader Method for Pharmaceutical Care on Patients with Bipolar I Disorder: Results from the EMDADER-TAB Study

Abstract: This study received funding from the Universidad de Antioquia, Committee for Development Research and Sustainability Program, CODI, (2013-2014 and 2014-2015). Humax Pharmaceutical provided support for the initial development of the EMDADER-TAB trial without commercial interest in the outcomes derived from the trial. Salazar-Ospina reports grants from Credito Beca Francisco José de Caldas Scholarship for Doctoral Programs (528), which also contributed to the support of this study. González-Avendaño is an employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
(18 reference statements)
1
15
1
1
Order By: Relevance
“…14 In comparison with the standard care, pharmaceutical care provides a reduction in the number of hospitalizations and emergency visits not only in patients with depression, but also in patients with bipolar disorder. 15 Rubio-Valera et al 9 found a probability of 0.71-0.75 for community pharmacy intervention vs usual care in depressed patients initiating treatment in terms of improved adherence level and Quality Adjusted Life Years (QALYs) to be cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…14 In comparison with the standard care, pharmaceutical care provides a reduction in the number of hospitalizations and emergency visits not only in patients with depression, but also in patients with bipolar disorder. 15 Rubio-Valera et al 9 found a probability of 0.71-0.75 for community pharmacy intervention vs usual care in depressed patients initiating treatment in terms of improved adherence level and Quality Adjusted Life Years (QALYs) to be cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…30,38,39,68 Outpatients in primary care, general mental health, and specialty clinics have improved medication safety (eg, reduction in anticholinergic burden, improved medication appropriateness) and reach therapeutic goals (eg, symptom reduction, fewer hospitalizations) at a higher rate when a pharmacist who is focused on CNS medications contributes to their care. 47,49,52,54,60,64,65 Patients filling prescriptions in community pharmacies have better access to long-acting injectable antipsychotic medications and increased medication adherence and are more satisfied with their medications when receiving pharmacist-delivered, psychiatry-focused interventions. [83][84][85][86] Patients seeking care for SUD experience increased access to buprenorphine-naloxone and naloxone, both life-saving medications, when a psychiatric pharmacist is involved in the SUD care setting.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, no previous randomized controlled trials exist that were designed to evaluate the effect of a clinical pharmacy practice model (CPPM) on the incidence of medication errors (patient safety), and thus, most of these strategies are based on expert recommendations and descriptive studies [8,28]. In Colombia, the first and only related RCT, Effectiveness of a Method for Pharmaceutical Care in outpatients with Bipolar disorder, showed the risk of hospitalizations and emergencies was lower for the intervention group [29]. This study is the first stepped-wedge controlled trial designed to assess the effect of the clinical pharmacy practice model on the incidence of medication error in hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%